Recent expansion and intensification of hypoxia in the Arabian Gulf and its drivers - Lachkar, Zouhair; Mehari, Michael; Lévy, Marina; Paparella, Francesco; Burt, John A. (Frontiers in Marine Science, 2022)
The Arabian Gulf (also known as Persian Gulf, hereafter Gulf) is a shallow semi-enclosed subtropical sea known for its extreme physical environment. Recent observations suggest a decline in oxygen concentrations in the Gulf over the past few decades accompanied by an expansion of seasonal near-bottom hypoxia. Here, we reconstruct the evolution of oxygen in the Gulf from 1982 through 2010 and explore its controlling factors. To this end, we use an eddy-resolving hindcast simulation forced with winds and heat and freshwater fluxes from an atmospheric reanalysis. We show that near-bottom hypoxia emerges in the deeper part of the Gulf over summer and peaks in autumn in response to enhanced vertical stratification inhibiting mixing and O2 replenishment at depth. We also find a significant deoxygenation in the Gulf over the study period, with the Gulf O2 content dropping by 1% per decade and near-bottom O2 decreasing by between 10 and 30 mmol/m3 in the deeper part of the Gulf between the early 1980s and the late 2000s. These changes result in the horizontal expansion of seasonal bottom hypoxia with the hypoxia-prone seafloor area increasing from less than 20,000 km2 in the 1980s to 30,000 km2 in the 2000s. The expansion of hypoxia is accompanied by a lengthening of the hypoxic season with hypoxia emerging locally 1 to 2 months earlier in the late 2000s relative to the early 1980s. Furthermore, declining O2 levels favor the expansion of suboxic conditions and the amplification of denitrification there. An analysis of the Gulf oxygen budget demonstrates that deoxygenation is essentially caused by reduced oxygen solubility near the surface and enhanced respiration near the bottom. While reduced solubility results from the warming of the Gulf waters, enhanced respiration is mostly driven by an increased supply of nutrients imported from the Arabian Sea due to the weakening of winter Shamal winds over the study period. Our findings suggest that recent changes in local climate are not only altering the Gulf physical environment but are also having a strong impact on the Gulf biogeochemistry with profound potential implications for the ecosystems and the fisheries of the region.